Journal of Environmental Analytical Chemistry - OMICS International (OMICS International, 2026)
Journal of Environmental Analytical Chemistry focus on specialisation in advanced modern analytical methodology to face various challenges in environmental chemistry and Analytical chemistry. The Journal covers area such as analytical instrumentation, techniques for remote measurements, determination of trace atmospheric constituents of anthropogenic and natural origin, detection and identification of chemical compounds in nature (air, water, soil and biota), determination and validation of heavy metals and radionuclides in the environment, different method and chemometrics in environmental analysis, environmental chemistry such as environmental monitoring, studies of the quality of water and pollutants contents of effluents.
Keywords: Química ambiental; Revistas depredadoras; Predatory journals